Assessing English poetry: a curriculum-centric examination of assessment beliefs and practices of lecturers - Chen, Shubin; Nimehchisalem, Vahid; Abdullah, Ain Nadzimah (Scientific Research Publishing, 2024)
This research investigates the complex interplay between curriculum and assessment in tertiary-level poetry education within English language instruction, recognizing poetry’s role in enhancing proficiency and cultural awareness. Employing a curriculum-centric approach, the study interviews 16 university English poetry lecturers through qualitative research to glean diverse perspectives. Rigorous validation methods, including peer debriefing and member checking, ensure robust findings. We employed thematic analysis, using NVivo 12 Plus, and followed Tyler’s Objective Model, to explore the impact of curriculum elements on assessment beliefs and practices. The study uncovers challenges faced by lecturers, strategies employed, and the influence of curricular structures on assessment approaches. Findings reveal a balance between curriculum requirements and fostering creativity in assessment, offering a comprehensive understanding of the intricate relationship between curriculum components and assessment beliefs and practices. Across five core components—teaching objectives, instructional methods, content and subject matter, assessment framework, and measurement—the study highlights key insights. Challenges arise from ambitious objectives or resource constraints, emphasizing realistic goal-setting. The research concludes that maintaining a balance for autonomy and adaptive strategies is crucial for effective poetry education practices. Continuous improvement, guided by feedback and professional development, is essential. These insights contribute to understanding for educators, curriculum developers, and policymakers, with implications for informing curriculum development, policy, and recommendations for professional development and curriculum reform efforts. This paper addresses a significant gap in understanding the impact of curriculum on poetry assessment beliefs and practices, contributing valuable insights to the broader discourse on language education and assessment.